Negative Pressure Wound Therapy of Chronically Infected Wounds Using 1% Acetic Acid Irrigation - Jeong, Hii Sun (Arch Plast Surg, 2015)
BACKGROUND: Negative-pressure wound therapy (NPWT) induces angiogenesis and collagen synthesis to promote tissue healing. Although acetic acid soaks normalize alkali wound conditions to raise tissue oxygen saturation and deconstruct the biofilms of chronic wounds, frequent dressing changes are required. METHODS: Combined use of NPWT and acetic acid irrigation was assessed in the treatment of chronic wounds, instilling acetic acid solution (1%) beneath polyurethane membranes twice daily for three weeks under continuous pressure (125 mm Hg). Clinical photographs, pH levels, cultures, and debrided fragments of wounds were obtained pre- and posttreatment. Tissue immunostaining (CD31, Ki-67, and CD45) and reverse transcription-polymerase chain reaction (vascular endothelial growth factor [VEGF], vascular endothelial growth factor receptor [VEGFR]; procollagen; hypoxia-inducible factor 1 alpha [HIF-1-alpha]; matrix metalloproteinase [MMP]-1,-3,-9; and tissue inhibitor of metalloproteinase [TIMP]) were also performed. RESULTS: Wound sizes tended to diminish with the combined therapy, accompanied by drops in wound pH (weakly acidic or neutral) and less evidence of infection. CD31 and Ki-67 immunostaining increased (P<0.05) post-treatment, as did the levels of VEGFR, procollagen, and MMP-1 (P<0.05), whereas the VEGF, HIF-1-alpha, and MMP-9/TIMP levels declined (P<0.05). CONCLUSIONS: By combining acetic acid irrigation with negative-pressure dressings, both the pH and the size of chronic wounds can be reduced and infections be controlled. This approach may enhance angiogenesis and collagen synthesis in wounds, restoring the extracellular matrix.